Protecting-group-free site-selective reactions in a metal–organic framework reaction vessel - Huxley, Michael T.; Burgun, Alexandre; Ghodrati, Hanieh; Coghlan, Campbell J.; Lemieux, Anthony; Champness, Neil R.; Huang, David M.; Doonan, Christian J.; Sumby, Christopher J. (American Chemical Society, 2018)
Site-selective organic transformations are commonly required in the synthesis of complex molecules. By employing a bespoke metal-organic framework (MOF, 1·[Mn(CO)3N3]), in which coordinated azide anions are precisely positioned within 1D channels, we present a strategy for the site-selective transformation of dialkynes into alkyne-functionalized triazoles. As an illustration of this approach, 1,7-octadiyne-3,6-dione stoichiometrically furnishes the mono-“click” product N-methyl-4-hex-5’-ynl-1’,4’dione-1,2,3-triazole with only trace bis-triazole side-product. Stepwise insights into conversions of the MOF reaction vessel were obtained by X-ray crystallography, demonstrating that the reactive sites are “isolated” from one another. Single-crystal to singlecrystal transformations of the Mn(I)-metalated material 1·[Mn(CO)3(H2O)]Br to the corresponding azide species 1·[Mn(CO)3N3] with sodium azide, followed by a series of [3+2] azide-alkyne cycloaddition reactions, are reported. The final liberation of the “click” products from the porous material is achieved by N-alkylation with MeBr, regenerating starting MOF 1·[Mn(CO)3(H2O)]Br, and the organic products characterized by NMR spectroscopy and mass spectrometry. Once the dialkyne length exceeds the azide separation, site selectivity is lost, confirming the critical importance of isolated azide moieties for this strategy. We postulate that carefully designed MOFs can act as physical protecting groups to facilitate other site-selective and chemoselective transformations.